Nutrient Saving and Yield Enhancement through Fertigation in Apple-Growing Cold Humid Regions of North-west Himalayas - O.C. Sharma, J. I. Mir, D.B. Singh, Wasim H. Raja; Sanjay Arora, Anil Sharma, Sarvendra Kumar Shiv Lal, Geetika Malik (Journal of the Indian Society of Soil Science, 2018)
In order to identify suitable fertigation techniques to get higher return from fertilizer application in applegrowing cold humid regions of north-west Himalayas, an experiment with different fertigation treatments was conducted at ICAR-Central Institute of Temperate Horticulture Farm, Srinagar. As regards yieldfertilizer ratio (YFR), the results suggested superiority of three fertigation treatments viz. 50% recommended fertilizer (RF) in one split, 50% RF in two splits and 75% RF in two splits over other treatments with value of YFR being 16.0, 15.7 and 14.3, respectively. Apple leaves and fruits exhibited highest macronutrient content with the application of 100% RF dosage in two splits. Results revealed that 25% of the RF could be saved along with increase in apple fruit yield on applying 75% of the RF in two splits through fertigation. The maximum apple yield, nutrient accumulation efficiency, macronutrient concentration in leaf and fruits was also observed in the aforesaid treatment.